2009
DOI: 10.1074/jbc.m807312200
|View full text |Cite
|
Sign up to set email alerts
|

RTX Calcium Binding Motifs Are Intrinsically Disordered in the Absence of Calcium

Abstract: The Repeat in Toxin (RTX) motif is a tandemly repeated calcium-binding nonapeptide sequence present in proteins that are secreted by the type I secretion system (T1SS) of Gram-negative bacteria. Here, we have characterized the structural and hydrodynamic properties of the RTX Repeat Domain (RD) of the CyaA toxin from Bordetella pertussis. This 701-amino acid long domain contains about 40 RTX motifs. We showed that, in the absence of calcium, RD was natively disordered, weakly stable, and highly hydrated. Calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
186
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(202 citation statements)
references
References 30 publications
15
186
1
Order By: Relevance
“…Circular Dichroism Spectroscopy-CD spectra were recorded on an Aviv circular dichroism spectrometer model 215, equipped with a water-cooled Peltier unit as described elsewhere (17). CD measurements were carried out at a scan rate of 0.5 nm/s (step, 0.5 nm; integration time, 1 s) with a time constant of 100 ms and a bandwidth of 1 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Circular Dichroism Spectroscopy-CD spectra were recorded on an Aviv circular dichroism spectrometer model 215, equipped with a water-cooled Peltier unit as described elsewhere (17). CD measurements were carried out at a scan rate of 0.5 nm/s (step, 0.5 nm; integration time, 1 s) with a time constant of 100 ms and a bandwidth of 1 nm.…”
Section: Methodsmentioning
confidence: 99%
“…These motifs constitute the main Ca 2ϩ binding sites of the protein (16). The RTX motifs are intrinsically disordered in the absence of calcium (17)(18)(19)(20). The intrinsic disorder predictors (21)(22)(23)(24) (Fig.…”
mentioning
confidence: 99%
“…This is consistent with the findings of Pimenta et al (2005) who showed that the amount of HlyA secreted and the activity of HlyA increased in line with the extracellular Ca 2+ concentration over a millimolar range. Chenal et al (2009) indeed proposed that Ca 2+ -dependent folding of the RTX region of emerging HlyA proteins could contribute a nucleus for folding of the more proximal regions of the protein. Intriguingly, the geometry of the HlyA molecule -with conceivably at least two distinct types of folding pathway triggers, positioned towards the C terminus of the protein -the RTX Ca 2+ repeats and the Cterminal end itself, suggest that the C terminus may lead the way out of the translocator.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Chenal et al (2009) and Sotomayor Perez et al (2010) recently showed that milimolar concentrations of Ca 2+ ions in vitro promote the compaction of the normally disordered RTX region of a type I protein, together with increased formation of stable secondary and tertiary structures. This is consistent with the findings of Pimenta et al (2005) who showed that the amount of HlyA secreted and the activity of HlyA increased in line with the extracellular Ca 2+ concentration over a millimolar range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation